previous up next
Go backward to Relationship
Go up to Top
Go forward to Proof (Continued)
RISC-Linz logo


forall x in C', y in C': cartesian(x *C' y) = cartesian(x) *C cartesian(y).
Take arbitrary x in C' and y in C'. We then have
cartesian(x *C' y) =
cartesian(x0y0, shift(x1+y1)) =
x0y0cos(shift(x1+y1)) + (x0y0sin(shift(x1+y1)))i = (*)
x0y0cos(x1+y1) + (x0y0sin(x1+y1))i.
(*) holds because of the definition "shift" and for every x in R,
sin(x+2 pi ) = sin(x),
cos(x+2 pi ) = cos(x)

Author: Wolfgang Schreiner
Last Modification: December 7, 1999

previous up next